A bZIP transcription factor (CiFD) regulates drought‐ and low‐temperature‐induced flowering by alternative splicing in citrus. Issue 3 (31st December 2022) - Ye, Li‐Xia; Wu, Yan‐Mei; Zhang, Jin‐Xia; Zhang, Jin‐Xin; Zhou, Huan; Zeng, Ren‐Fang; Zheng, Wei‐Xuan; Qiu, Mei‐Qi; Zhou, Jing‐Jing; Xie, Zong‐Zhou; Hu, Chun‐Gen; Zhang, Jin‐Zhi
ABSTRACT: Drought and low temperature are two key environmental factors that induce adult citrus flowering. However, the underlying regulation mechanism is poorly understood. The bZIP transcription factor FD is a key component of the florigen activation complex (FAC) which is composed of FLOWERING LOCUS T (FT), FD, and 14‐3‐3 proteins. In this study, isolation and characterization of CiFD in citrus found that there was alternative splicing (AS) of CiFD, forming two different proteins (CiFDα and CiFDβ). Further investigation found that their expression patterns were similar in different tissues of citrus, but the subcellular localization and transcriptional activity were different. Overexpression of the CiFD DNA sequence ( CiFD ‐DNA), CiFDα, or CiFDβ in tobacco and citrus showed early flowering, and CiFD ‐DNA transgenic plants were the earliest, followed by CiFDβ and CiFDα . Interestingly, CiFDα and CiFDβ were induced by low temperature and drought, respectively. Further analysis showed that CiFDα can form a FAC complex with CiFT, Ci14‐3‐3, and then bind to the citrus APETALA1 ( CiAP1 ) promoter and promote its expression. However, CiFDβ can directly bind to the CiAP1 promoter independently of CiFT and Ci14‐3‐3. These results showed that CiFDβ can form a more direct and simplified pathway that is independent of the FAC complex to regulate drought‐induced flowering through AS. In addition, a bHLH transcription factor (CibHLH96) binds to CiFD promoter and promotes the expression of CiFD under drought condition. Transgenic analysis found that CibHLH96 can promote flowering in transgenic tobacco. These results suggest that CiFD is involved in drought‐ and low‐temperature‐induced citrus flowering through different regulatory patterns. Abstract : In citrus, alternative splicing of the transcription factor gene CiFD produces two different proteins, CiFDα and CiFDβ At low temperature, CiFDα forms a complex with CiFLOWERING LOCUS T and Ci14‐3‐3 to activate the expression of CiAPETALA1 . Under drought conditions, CiFDβ directly binds to the CiAPETALA1 promoter to induce flowering.